Integrasi Outcome-Based Education dan Problem-Based Learning dalam Meningkatkan Kemampuan Kolaboratif Mahasiswa pada Pembelajaran Anatomi - Dini Annisha; Yossie Ulfa Nuzalifa; Febry Rahmadhani Hasibuan; Hasbiah Hasbiah (Universitas Negeri Medan, 2026)
This study aims to examine the effectiveness of integrating Outcome-Based Education (OBE) and Problem-Based Learning (PBL) in improving students’ collaborative skills in the anatomy course in the Physical Education Program at the Indonesian National Islamic University (UNIKI). This study used a quantitative pre-experimental approach with a one-group pretest-posttest design to test the effectiveness of integrating Outcome-Based Education (OBE) and Problem-Based Learning (PBL) in improving students' collaborative skills. The research sample consisted of 33 students selected using saturation sampling. The results showed a statistically significant increase in collaborative skills after the intervention (t(32) = 15.673; p < 0.001), with the mean increasing from 3.12 (moderate category) to 4.28 (high category). The effect size was classified as very large (Cohen’s d = 2.73), indicating that the intervention had a very high practical impact. The distribution of students also shifted significantly, from 97% in the moderate category to 100% in the high category. These findings confirm that the synergy between OBE and PBL is an effective pedagogical strategy for simultaneously enhancing and equalizing students’ collaborative skills in an inclusive mannerelementary school students’ learning motivation and critical thinking skills.